2019
DOI: 10.1248/bpb.b18-00688
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Animal Model of Induced Breast Precancerous Lesion in Tree Shrew

Abstract: Chinese tree shrew, an animal exhibited closer evolutionary relationship with humans compared to rodents, is getting increasingly attentions as an appealing experimental animal model for human diseases. However, a high-efficiency and stable method to establish tree shrew breast precancerous lesions model has not been clearly elucidated. Thus, the current study aimed to explore the way of establishing breast precancerous model in tree shrew and investigate the pathologic characteristics of induced breast precan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Chile and Jordan have reported a decrease in anti-HAV sero-prevalence over the years [89,91]. The study conducted in Jordan showed a continual rise of the seroprevalence rates with rise in age.…”
Section: The World Scenario -Hav Sero-prevalencementioning
confidence: 93%
See 1 more Smart Citation
“…Chile and Jordan have reported a decrease in anti-HAV sero-prevalence over the years [89,91]. The study conducted in Jordan showed a continual rise of the seroprevalence rates with rise in age.…”
Section: The World Scenario -Hav Sero-prevalencementioning
confidence: 93%
“…The study conducted in Jordan showed a continual rise of the seroprevalence rates with rise in age. While, sero-prevalence was 26% among <2 years old, the rate increased to a whooping 94% for >20 years old [91]. A study conducted in Western Brazil revealed overall sero-prevalence among children as 16.7% in the year 2011, which significantly increased to 70.45% in a recently conducted survey [52,91].…”
Section: The World Scenario -Hav Sero-prevalencementioning
confidence: 99%
“…Chinese tree shrew (Tupaia belangeri chinensis), mainly distributing in Yunnan and Guangxi provinces in China, is a class of small animals having a closer evolutionary relationship with humans compared to rodents [91]. Tree shrews have emerged in the vision of scientists for more than 30 years as a result of having many valuable features that are suitable in animals utilized as experimental models in biomedical studies [92], particularly in the fields of toxicology and virology [93].…”
Section: Tree Shrewsmentioning
confidence: 99%
“…In recent years, several virus infection models, including influenza B [8], Zika virus [9], hepatitis C virus [10], and avian H5N1/ H9N2 influenza viruses [11,12], have been investigated by using tree shrews. Other human diseases, such as retinal vein pulsation and glaucoma of the visual system [13][14][15], myocardial ischemia and atherosclerosis of the cardiovascular system [16,17], nonalcoholic fatty liver [18], diabetic nephropathy [19] and obesity [20] of metabolism, cancers [21,22], Alzheimer's disease [23] and depression [24], all used tree shrews as disease models for their studies. However, the characteristics of ACE2, TMPRSS2 and TMPRSS4 in tree shrews have not been reported in most tissues or organs, and organs are more at risk for SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%